PENGUJIAN INFILTRASI FINAL CLAY COVER PADA BANGUNAN SANITARY LANDFILL - galung, erwin (Universitas Negeri Makassar, 2014)
ABSTRACT The aim of the study is to analyze the physical characteristic of PCC cement variation used as final clay cover at sanitary landfill through column model testing of final clay cover infiltration. The result showed clay plasticity (CL) stabilization is low with cement variation of 0%, 5%, 10%, 15%, and 20% at column infiltration model. The highest infiltration (460 cmÂ³/minute) is detected at clay without any cement stabilization while the lowest is for the 10% concentration with result of 23 cmÂ³/minute. Its permeability decreases with the increase of cement concentration to as high as 10%. Permeability coefficient value (k) for 0% cement is 7,71 x 10-5 cm/second and 7,46 x 10-6 cm/second and 1,51 x 10-7 cm/second for cement concentration of 5% and 10%, respectively. However for concentration above 10%, the permeability coefficient value increases as high as 1,67 x 10-6 cm/second and 2,04 x 10-5 cm/second for cement concentration of 15% and 20%, respectively. Thus, from this study it can be concluded final clay cover for sanitary landfill can be used with various cement concentration up to 10%. Keywords: bleeding, density factor and slump value